Polyphenolic and molecular variation in Thymus species using HPLC and SRAP analyses - Danial Sarfaraz (Nature Portfolio, 2021)
Abstract In the present research, inter and intra genetic variability of 77 accessions belonging to 11 Thymus species were assessed using eight SRAP primer combinations. High polymorphism (98.3%) was observed in the studied species. The cluster analysis classified Thymus species into five main groups. According to molecular variance (AMOVA) analysis, 63.14% of total genetic variation was obtained within the species, while 36.86% of variation was observed among species. STRUCTURE analysis was also performed to estimate the admixture of species. For instance, T. carmanicus and T. transcaspicus revealed high admixtures. HPLC analysis also demonstrated the presence of rosmarinic acid (32.3–150.7 mg/100 g DW), salvianolic acid (8–90 mg/100 g DW), and cinnamic acid (1.7–32.3 mg/100 g DW) as major phenolic acids, as well as apigenin, epicatechin, and naringenin as the major flavonoids. The highest phenolic and flavonoid contents were detected in T. transcaspicus (37.62 mg gallic acid equivalents (GAE) g−1 DW) and T. vulgaris (8.72 mg quercetin equivalents (QE) g−1 DW), respectively. The antioxidant properties and total phenolic of Thymus species were examined using DPPH and β-carotene-linoleic acid model systems and consequently T. vulgaris and T. pubescens were detected with the highest and the lowest antioxidant activities respectively. Cluster and principal Components Analysis (PCA) of the components classified the species in to three groups. Finally, similarity within some species was observed comparing molecular and phytochemical markers. For instance, T. vulgaris separated from other species according to major polyphenolic profiles and molecular analyses, as well as T. transcaspicus, T. carmanicus, and T. fedtschenkoi that were clustered in the same groups.